Analisis pendapatan usaha peternakan babi melalui program pengembangan kecamatan di Kabupaten Sikka=Income Analysis of Pig Farming Through Subdistrict Development program in Sikka Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Credit was useful for farmer capital to increase their farming input. Through the existence of credit the productivity and the income of farmer would be increasing. This research was carried out in Nita and Alok sub district, Sikka regency, on July until September 2004. The objective of this study was to calculate the operational efficiency and the income of pig farming, before getting credit and after getting credit in loan degrees of Rp. 500,000 until Rp. 1,500,000 (credit A) and Rp. 2,000,000 until Rp. 3,000,000 (credit B) and to analyze the influencing factors of income. The material of the study was pig farmers who received credit facility which chosen by purposive and stratified random sampling. Variables which was investigated includes the cost and farm receiving, business scale, mortality, pig species, the value of credit, invesment value and the experience in pig farming. Survey was applied to collect the data and the data were analyzed by multiple regression model, student t test and the quantitative descriptive analysis. The result of the study showed that: 1). The income of pig farming after credit was relatively the same to the income before credit at level of the loan from Rp 500,000 until Rp 1,500,000